ANALISIS PENYUSUNAN LAPORAN KEUANGAN PADA UMKM KAWASAN KERATON ISTANA SURYA NEGARA DI KABUPATEN SANGGAU - Savira, Revi; Kristiawati, Endang; Afif, Ali (Jurnal Akuntansi, Auditing dan Investasi, 2022)
This research focuses on the discussion of the preparation of financial statements in MSMEs in the Keraton Istana Surya Negara Area in Sanggau Regency which aims to describe how and the factors faced by MSME actors and the design of MSME financial statements based on SAK EMKM. This research is a qualitative research with a descriptive approach. The data collection technique uses the interview method to the speakers, with the population and samples, namely msME actors in the Keraton Istana Surya Negara Area in Sanggau Regency. The data analysis techniques used are Indepth Interview (in-depth interview) and SAK EMKM.Based on the results of this study in the process of preparing financial reports in the Palace Area of the Keraton Istana Surya Negara, it shows that they have not implemented financial statements based on SAK EMKM. Let alone the recording of financial statements based on SAK EMKM, even simple bookkeeping does not exist, plus the average educational background condition is only elementary school graduates and some other high schools. In running a business, MSME actors never store or record evidence of transactions that occur every day. Thereason is that a preparation of financial statements is used so that MSME actors can find out the ability and capacity of the business for planning their future business development.